1993
DOI: 10.1002/jbm.820270615
|View full text |Cite
|
Sign up to set email alerts
|

Detection of remnant proteolytic activities in unimplanted glutaraldehyde‐treated bovine pericardium and explanted cardiac bioprostheses

Abstract: The presence and activity of proteolytic enzymes has been investigated in vitro on soluble and insoluble preparations obtained from both unimplanted and implanted glutaraldehyde-treated bovine parietal pericardium. Using detection by colorimetric techniques, soluble preparations were shown to hydrolyze enzyme substrates that are characteristic for trypsin-like proteases, cathepsin-like proteases, and collagenase. As detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis in gradient gels and gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Both MMP-2 and MMP-9 were shown to be involved in the progression of atherosclerotic plaque 8 and in calcification of glutaraldehyde fixed heterograft bioprosthetic heart valves. 15 In our cell culture studies using AVICs cultured on a collagen gel in the presence of TN-C, we observed a seven-to eightfold increase in MMP-2 mRNA expression ( Figure 3A), and the gelatinolytic activity of MMP-2 was also increased ( Figure 3B), which suggests that the accumulation of TN-C around calcific regions may up-regulate the expression of MMP-2. The fact that most of the secreted MMP-2 (in conditioned medium) was in the pro form, and the active form of MMP-2 was associated with cells in cell lysates ( Figure 3B) may help explain our observations in the clinical aortic valve retrievals, that most MMP-2 was in its pro form (Figure 2).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Both MMP-2 and MMP-9 were shown to be involved in the progression of atherosclerotic plaque 8 and in calcification of glutaraldehyde fixed heterograft bioprosthetic heart valves. 15 In our cell culture studies using AVICs cultured on a collagen gel in the presence of TN-C, we observed a seven-to eightfold increase in MMP-2 mRNA expression ( Figure 3A), and the gelatinolytic activity of MMP-2 was also increased ( Figure 3B), which suggests that the accumulation of TN-C around calcific regions may up-regulate the expression of MMP-2. The fact that most of the secreted MMP-2 (in conditioned medium) was in the pro form, and the active form of MMP-2 was associated with cells in cell lysates ( Figure 3B) may help explain our observations in the clinical aortic valve retrievals, that most MMP-2 was in its pro form (Figure 2).…”
Section: Discussionmentioning
confidence: 76%
“…[15][16][17] In addition, it has been demonstrated, in vascular smooth muscle cells, that degradation of type I collagen by MMPs promotes TN-C expression at the transcriptional level. 18 Conversely, TN-C also up-regulates the expression of MMPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proteases that cause structural collagen damage in other cardiovascular tissues 35,36 have been identified in pericardial heart valves. 37 However, the nature of in vivo structural defects identified in the present study and the substantial correlation with in vitro studies and others discussed below suggest that the mechanical effects dominate in the degradation of the extracellular matrix.…”
Section: Mechanisms Of Noncalcific Damagementioning
confidence: 72%
“…13,14 For example, subdermally implanted glutaraldehyde-treated bovine parietal pericardium contains an array of extracellular matrix protein-degrading proteinases including serine proteinases and MMPs. 13,14 High concentrations of MMPs are also present in atherosclerotic plaques 15 and in restenotic lesions. 16 Tenascin-C (TN-C) is an extracellular matrix glycoprotein with a highly restricted pattern of gene expression, but it is prominently expressed in embryonic and adult tissues that are actively remodeling.…”
mentioning
confidence: 99%